Premises for Optimizing the Method of Bone Marrow Cryopreservation in Animals with Autoimmune Pathologies - Kozlova, Yu. A.; Goltsev, A. N.; Dubrava, T. G.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2004)
There were determined the functional characteristics of bone marrow cells (BM) in healthy animals and donors with autoimmune diseases (AID) prior to and following cryopreservation. The studies demonstrated that independently on the type of autoimmune pathology, the maximum amount of hemopoietic precursors of granulomonocytopoesis (CFU-GM) in BM was reached during its cryopreservation under the protection of 7% DMSO. For BM cells of intact animals the same integrity of CFU-GM was obtained when using DMSO in 10% concentration.